Exposure to particles in veterinary clinical practice: exploratory study - Viegas, Susana (2018)
Several papers have reported that livestock workers have an inv«creased risk of developing respiratory diseases as a result of chronic inhalation exposure to organic dust in farm animal production facilities. However, for veterinarians, most of the published studies are related to zoonoses and only a few papers have been dedicated to occupational health in small-animal veterinary practices. An exploratory study was developed aiming to perform a first assessment in the particles contamination and to identify the presence of other risk factors that should be tackled in future studies.